The development of self-management of secondary schools from the point of view of manager - Ahmed, Dr. May Faisal (The journal of contemporary issues in business and government, 2021)
A field study aimed to knowing the development of self-management of secondary schools from the point of view of principals. The research adopted the descriptive analytical method. The research community consists of (249) male and female principals, and the research sample was chosen by simple random method, at a rate of (50%) from the original research community, as the number of sample individuals reached (125) principals. A questionnaire was built that included (36) items distributed among the fields of (preparation and arrangements, principles and goals, laws and the participation and responsibilities, implementation, follow-up and evaluation). The researcher made sure of their sincerity and reliability and the results of the research data were analyzed using the (SPSS) program, and came to the most important results: “The general average for the four fields was a weighted mean (2.624) and a percentage weight (87.466%), which is a very good result in developing self-management in secondary schools in Baghdad governorate and that the field of implementation, follow-up and evaluation was ranked first, followed by the field of preparation and arrangements. As for the fields of laws, participation and responsibilities, it won the third place, followed by the field of principles and objectives in the fourth place, and in conclusion the research proved a number of recommendations and proposals.